(untitled) (Economic and Political Thought, 2024)
The article discusses the key aspects of Donald Trump’s election campaign that led to his victory in the 2024 US presidential election. The authors point out that this campaign was one of the most polarized in the history of the United States, and its success was based on a populist message, strong personalization of communication, and modern technologies such as social media, big data, and artificial intelligence. Trump effectively mobilized his electorate, using disinformation, emotional rhetoric, and criticism of opponents, which was particularly effective in the so‑called „swing states” that determined his victory. The support of influential people also played a significant role. Despite many controversies and legal problems, Trump won as many as 312 electoral votes, with a small advantage in the popular vote. The analysis also draws attention to the changing structure of the electorate, especially the growing support among Latinos and African Americans, and to campaign financing, which, although lower than that of the competition, was effectively used. The article highlights the need to adapt the US electoral system to new realities, including increasing transparency in the use of technology, and the possible need for electoral system reform. The 2024 election has been considered a breakthrough and provides important guidelines for future political campaigns in the US.